Uji Kemampuan Penghambatan Ekstrak Biji Nyiri(Xylocarpus Granatum) Terhadap Jamur Benih Tanaman Kehutanan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
ABSTRACT Deterioration of seeds due to disease attack is a common problem in the most nurseries of forest plants. Disease control on seeds is still applied using synthetic pesticide. The aplication of the synthetic pesticide, instead of expensive, develops side effect i.e. environmental polution, diminish seed germination and shorten the life cycle of seed. The aim of the experiment was to know the potential of seed extract of Xylocarpus granatum as phyto fungicide to inhibit the infection of fungi on some forest trees seed. This experiment was carried out in vivo and in vitro at the Faculty of Forestry Gadjah Mada University Yogyakarta. X. granatum seed was extracted in water and ethanol to produce phyto fungicide and then was tested on 3 kinds of seed of Pinus merkusii, Paraserianthes faicatari a, and Acacia mangium that had been inoculated with pathogen Fusarium sp. (isolated from P merkusii seed), Aspergilus sp. (isolated from P falcataria seed) and Aspergilus sp. (isolated from A. mangium seed), respectively The concentration of the extract were 0, 1 and 5 mg powder ofX. granatum/ml liquid. This factorial experiment was arranged in a Completely Randomized Design with three variables. The respons of treatments were percentage of seed infected by fungi, percentage of seed germination, the percentage of spore germination and the length of mycelia. The results of the experiment showed that X. granatum extract significantly inhibited the development of the fungi tested as indicated by the diminution of infected seed, fungal spore germination and mycelial growth. It was concluded that X. granatum seed contained natural substance potential as phyto fungicide. Key words: Xylocarpus granatum, seed trees pathogen, phyto fungicide